The Blackwell Companion to Hinduism
DOI: 10.1002/9780470998694.ch20
|View full text |Cite
|
Sign up to set email alerts
|

The Science of Medicine

Abstract: Indian medicine, as a systematic and scholarly tradition, begins historically with the appearance of the great medical encyclopedias of Caraka, Suśruta and Bhela about two thousand years ago. 1 These are the oldest Indian medical texts we have, and also the most influential. Just as Pān . ini's famous linguistic study of Sanskrit leaps into the historical record fully formed, like the Buddha from Queen Maya's side, so the medical encyclopedias too emerge with a learned medical tradition in an almost fully arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…In this context, it is to be noted that the scholars of ancient Greek medicine considered the four humors to be the regulators of all physiological processes: 1) blood, 2) phlegm, 3) yellow bile, and 4) black bile. In fact, it is actually on this similarity that historians compare Ayurveda theories with ancient Greek medical theories (7,34). Most of the historians have suggested the possibility of various interactions having taken place between the scholars of ancient Greece and ancient India, especially when Alexander the Great (326 BCE) visited the places around Taxila, one of the ancient seats of learning (3).…”
Section: Physiology and Ayurvedamentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it is to be noted that the scholars of ancient Greek medicine considered the four humors to be the regulators of all physiological processes: 1) blood, 2) phlegm, 3) yellow bile, and 4) black bile. In fact, it is actually on this similarity that historians compare Ayurveda theories with ancient Greek medical theories (7,34). Most of the historians have suggested the possibility of various interactions having taken place between the scholars of ancient Greece and ancient India, especially when Alexander the Great (326 BCE) visited the places around Taxila, one of the ancient seats of learning (3).…”
Section: Physiology and Ayurvedamentioning
confidence: 99%
“…A few historians, on the other hand, have suggested that such interactions must have taken place even before Alexander the Great visited India (9,17). One cannot deny the fact that there are striking similarities between some of the theories in these two streams of medical knowledge; however, the question as to "which system got influenced by the other" has been a matter of debate, as no system mentions these facts (7,24,34). Whatever may be the case, it is to be noted that the theory of Tridosha is not simply a "humoral theory"; rather, it is based on a considerably precise understanding of homeostatic principles (29).…”
Section: Physiology and Ayurvedamentioning
confidence: 99%
“…Whose religion?” and expand the conversation to include not just variations of Western thought, but also Eastern knowledge traditions. I cannot elaborate on specific elements within the history of Indian science here, but the reference list features numerous sources for comprehensive coverage of Ayurveda (Engler 2003; Frawley 2000; Larson 1987; Manohar 2008; Wujastyk 2003) and other Indian sciences (Arnold 2000; Bose, Sen, and Subbarayappa 2009; Chattopadhyaya and Kumar, 1995; Gosling 1976, 2001; Gupta and Sharma 2002; Hayashi 2003; Kumar 2006; Paranjape 2008; Prakash 1999; Raman 2006; Seal 1915; Sinha 1970).…”
Section: The State Of the Fieldmentioning
confidence: 99%
“…It is based on the doctrine of three bodily humours – wind, bile and phlegm – and on an understanding of disease as resulting from the aggravation of one or more of these humours, leading to blockages in the system. Diseases in their early stages are treated through dietary adjustments and alterations in lifestyle; at more advanced stages, they are treated by administering medicines which are mainly herbal, and by using a range of therapies including massage, enema, purgation, emesis, douching, sudation and minor surgery (Wujastyk 1993, 2003a,b).…”
mentioning
confidence: 99%
“…Ayurveda has both preventative and remedial aspects. It offers a great deal of practical advice on almost every aspect of day‐to‐day living (Alter 1999; Wujastyk 2003a,b) and places great emphasis on moderation in all one’s activities, desires and ambitions. Ayurveda is very much a living tradition in much of the Indian subcontinent, and constitutes an important part of the conceptual universe of most Indians and Sri Lankans.…”
mentioning
confidence: 99%